2010
DOI: 10.1002/ptr.3151
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of valerenic acid after single and multiple doses of valerian in older women

Abstract: Insomnia is a commonly reported clinical problem with as many as 50% of older adults reporting difficulty in falling and/or remaining asleep. Valerian (Valeriana officinalis) is a commonly used herb that has been advocated for promoting sleep. Valerenic acid is used as a marker for quantitative analysis of valerian products with evidence of pharmacological activity relevant to the hypnotic effects of valerian. The objective of this study was to determine the pharmacokinetics of valerenic acid in a group of eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The high V z of 6-10 L • kg −1 suggested that the compound was rapidly taken up by body tissues. Compartmental analysis revealed that the apparent volume of distribution in steady state This assumption is supported by the data of Anderson et al [10] who found a considerable inter-and intra-subject variability in the PK parameters of VA where C max and AUC decreased and t 1/2 increased with increasing body weight. The authors, therefore, speculated that higher doses of valerian were needed in patients with a higher body weight.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…The high V z of 6-10 L • kg −1 suggested that the compound was rapidly taken up by body tissues. Compartmental analysis revealed that the apparent volume of distribution in steady state This assumption is supported by the data of Anderson et al [10] who found a considerable inter-and intra-subject variability in the PK parameters of VA where C max and AUC decreased and t 1/2 increased with increasing body weight. The authors, therefore, speculated that higher doses of valerian were needed in patients with a higher body weight.…”
supporting
confidence: 59%
“…Until now, detailed pharmacokinetic data of VA are lacking. In a recent study Anderson et al [10] determined plasma levels of valerenic acid in older women after oral administration of single and multiple doses (300 mg) of a commercial valerian root preparation standardized to 0.8 % VA. The authors found no differences in the average peak Abstract !…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…216,217 Unfortunately, the FDA does not regulate their production, and the various formulations contain different amounts of valerian. 216,218 Although the exact mechanism of valerian for insomnia is unknown, it is believed to have important interactions with the neurotransmitter GABA and its receptors. Valerian is thought to inhibit the uptake of GABA and also stimulate its release.…”
Section: Valerianmentioning
confidence: 99%
“…The relatively wide variability in drug elimination half-life among individuals gives valerian an apparently low average efficacy. 46 However, outcomes for empirically treated clinical patients are probably better than those of drug trial volunteers, who are usually treated with a single dose or a limited range of doses.…”
Section: Editorialmentioning
confidence: 99%